2024
DOI: 10.1126/science.adj3484
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and heterologous reconstitution of Taxus biosynthetic enzymes leading to baccatin III

Bin Jiang,
Lei Gao,
Haijun Wang
et al.

Abstract: Paclitaxel is a well-known anticancer compound. Its biosynthesis involves the formation of a highly functionalized diterpenoid core skeleton (baccatin III) and the subsequent assembly of a phenylisoserinoyl side chain. Despite intensive investigation for half a century, the complete biosynthetic pathway of baccatin III remains unknown. Here, we identified a bifunctional cytochrome P450 enzyme (Taxane oxetanase, TOT) that catalyzes an oxidative rearrangement in paclitaxel oxetane formation, representing a previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Interestingly, recent studies suggested that the T5OH intermediate may undergo further oxidation by CYP725A4, leading to the formation of an oxetane intermediate . However, another recent work demonstrated that the generation of the oxetane intermediate is mediated by another novel P450 enzyme . The mechanism of the oxetane formation is worthwhile to gauge with QM/MM in our future work.…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, recent studies suggested that the T5OH intermediate may undergo further oxidation by CYP725A4, leading to the formation of an oxetane intermediate . However, another recent work demonstrated that the generation of the oxetane intermediate is mediated by another novel P450 enzyme . The mechanism of the oxetane formation is worthwhile to gauge with QM/MM in our future work.…”
Section: Discussionmentioning
confidence: 87%
“…The full names of abbreviations are listed as: GGPPS, geranylgeranyl diphosphate synthase; TXS, Taxadiene synthase; T5αOH, taxane 5α-hydroxylase; TAT, taxadien-5α-ol-O-acetyl-transferase; T13αOH, taxane 13α-hydroxylase; T10βOH, taxane 10β-hydroxylase; T14βOH, taxane 14β-hydroxylase; T2αOH, taxane 2α-hydroxylase; T7βOH, taxane 7β-hydroxylase; TBT, taxane 2α-O-benzoyl transferase; DBAT, 10-deacetyl-baccatin III-10-Oacetyltransferase; PAM, phenylalanine aminomutase; BAPT, 13-O-(3-amino-3-phenylpropanoyl) transferase; DBTNBT, 30-N-debenzoyl-20-deoxytaxol-Nbenzoyltransferase. The metabolic processes were adapted from previous reports ( Croteau et al., 2006 ; Cheng et al., 2021 ; Zhang et al., 2023 ; Jiang et al., 2024 ).…”
Section: Resultsmentioning
confidence: 99%
“…Six previously characterized Taxus genes can coordinatively produce key paclitaxel intermediates and serves as a crucial platform for the discovery of the remaining biosynthetic genes ( Liu et al., 2024 ). The screening strategy for the biosynthesis pathway of paclitaxel is constantly being updated, new enzyme genes like TOT1 and T9αH1 were innovatively proposed and precisely located in the synthesis pathway ( Jiang et al., 2024 ). In our study, most of the known genes involved in paclitaxel biosynthesis are located on an 80.46-Mb region and a 141.69-Mb region on chromosome 9, which were consistent with previous studies, and the number of identified enzyme genes in the clusters also increased ( Supplementary Table 3 ; Xiong et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent enzymatic actions include the conversion of l -dopa to betalamic acid by dopa-4,5-dioxygenase enzyme (DOD) and the glycosylation of cyclo -dopa at the 5- O position by the cyclo -dopa 5- O -glucosyltransferase (CDGT), ultimately resulting in the synthesis of betanin through the spontaneous condensation of the cyclo -dopa-5- O -glucoside with betalamic acid. The burgeoning field of synthetic biology has provided platforms for the production of complex natural products, with successful examples including the precursors of paclitaxel, artemisinin, and vincristine, which offers a viable solution to overcome the constraints associated with plant extraction method by genetically engineering biosynthetic pathways in microbes. Betanin bioproduction in Saccharomyces cerevisiae with an initial titer of 17 mg/L was achieved by introducing betanin biosynthetic pathway from plants .…”
Section: Introductionmentioning
confidence: 99%